Radiation dose reduction in adult abdorvien and pelvis CT scan - Jasmaniah, Abdul Majid (2009)
CT scan is an extremely valuable tool as it yields a lot of information regarding the internal human anatomy. Now with future advances in scanner technology the number of CT examination will likely continue to rise. Among all CT abdomen and pelvis have the highest effective dose. Thus it is important to minimize the dose by adjusting scanning parameter. Major technical factors that influence radiation dose from CT scan include tube voltage, tube current, scanning time, pitch, slice thickness and scanning volume. In this study only the tube current (mAs) is adjusted to as minimum as possible while the other factors are kept constant. The aim of this study is to determine whether a lower radiation dose could be used in adult abdomen and pelvis CT scan without affecting the diagnostic accuracy of the images. This is a randomised cross sectional prospective trial. Age, gender and abdominal dimension were recorded from 82 adult patient who underwent contrasted abdomen and pelvis CT scan from April 2008 until October 2008. 41 patients underwent CT at 240 mAs (control group), and 41 at 180 mAs (trial group-25% dose reduction). The anatomic details, image quality and the degree of confidence in reaching a diagnosis were graded as a scale of 1 (unsatisfactory) to 4 (excellent). The difference in perceived image quality between the control and trial group was not statistically significant (p=O.l4). There is no significant difference in image quality score in patient with transverse abdominal diameter <34.5 em and ~34.5 em (p=0.20). There is also no significant difference in image quality score in patient with cross sectional abdominal area < 800 cm2 and ~ 800 cm2 (p=O. 72) 25% dose reduction can be achieved in adult abdomen and pelvis CT scan if performed at 180 mAs, without deterioration of diagnostic image quality.